THE STRUCTURE AND CONTENT OF THE ELEMENTARY MATHEMATICS COURSE FOR ENTERING THE SPECIALTY - Ergasheva Matluba Burkhanovna (Zeta Repository, 2023)
The development of the movement to reform mathematics teaching in secondary school depends on the following actions: "the effort to bring the school mathematics course closer to modern mathematics and its practical applications; Struggle to create a unified mathematics course that combines arithmetic with fundamentals of algebra and geometry; The practical orientation of the school mathematics course, the connection of teaching with life, and the attention paid to the calculation culture of students, especially the theoretical side of the school mathematics course with serious implementation at the lower level of education, increased attention to the theoretical side of the school mathematics course etc.